Combined Arthroscopic Wafer Procedure and Triangular Fibrocartilage Complex Debridement versus Ulnar Shortening Diaphyseal Osteotomy in Management of Ulnar Impaction Syndrome: A Randomized Clinical Trial - El-Tayar, Ahmed; El-Ghandour, Samir; Ghazal, Adel; Rakha, Ibrahim; Sallam, Asser (Journal of Wrist Surgery, 2023)
Background The literature presents great challenge in comparing the arthroscopic wafer procedure (AWP) versus ulnar shortening osteotomy (USO) in the treatment of ulnar impaction syndrome (UIS).Purpose We aimed primarily to compare the clinical and functional outcomes of AWP with triangular fibrocartilage complex (TFCC) debridement versus USO in the management of UIS.Methods The study was conducted as a randomized clinical trial including 43 patients with UIS whose ulna variance was less than 4 mm. Patients were randomly allocated to either the AWP group (21 patients) who underwent AWP and TFCC debridement or the USO group (22 patients) who underwent diaphyseal USO. Patients were followed up for at least 12 months. The primary outcome measure was the Modified Mayo Wrist (MMW) score. The Disabilities of the Arm, Shoulder, and Hand (DASH) score, the mean operative time, postoperative complications, and patient satisfaction were our secondary outcomes.Results Radiological correction of variance was achieved in all patients. The mean operative time was significantly shorter in the AWP group. The postoperative MMW and DASH scores were better in the AWP group than in the USO group. Fewer complications occurred in the AWP group (1 of 21 patients) compared with the USO group (3 of 22 patients).Conclusions AWP with TFCC debridement is a reliable and safe method for the management of UIS with a positive variance of less than 4 mm with better clinical and functional results than diaphyseal USO.Type of study/level of evidence Therapeutic type II.
Keywords: wafer procedure; ulnar shortening; ulnar impaction; arthroscopic wafer; ulnar positive variance